The Polish elections to the European Parliament in 2014 as shown in the Polish press - Barabasz, Adam (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The paper presents the opinions of Polish journalists on the results of the elections to the European Parliament in Poland in 2014. The paper discusses the style of the election campaigns conducted by the different political parties. It also assesses the degree to which politicians and society were involved in the European elections. The paper presents the profiles of EP members published in the Polish press. The analysis is conducted on the basis of articles published from April 15 till May 27, 2014 in “Gazeta Wyborcza”, “Rzeczpospolita”, “Zielony Sztandar”, “Przegląd”, “Gazeta Polska”, “Najwyższy Czas”, “Polityka”, “Wprost” and “Newsweek”.

W artykule zaprezentowano opinie publicystów prasy polskiej na temat wyników wyborów do Parlamentu Europejskiego przeprowadzonych w Polsce w 2014 roku. W artykule zwrócono uwagę na style prowadzenia kampanii wyborczej przez partie polityczne. Oceniono także stopień zaangażowania polityków oraz społeczeństwa w Eurowybory. Opisano również sylwetki eurodeputowanych przedstawiane w prasie polskiej. Analizy dokonano na podstawie artykułów opublikowanych w dniach 15.04-27.05.2014 r. na łamach: “Gazety Wyborczej”, “Rzeczpospolitej”, “Zielonego Sztandaru”, “Przeglądu”, “Gazety Polskiej”, “Najwyższego Czasu”, “Polityki”, “Wprost” oraz “Newsweeka”.
Prasa polska o wyborach do Parlamentu Europejskiego w Polsce w 2014 roku
Keywords: European Parliament; political parties; European election; election campaign; MEPs; Polish press; Parlament Europejski; partie polityczne; Eurowybory; kampania wyborcza; Eurodeputowani